Sustainability Goals and Supply Chain Due Diligence Laws - Felix Bierbrauer (Wirtschaftsdienst)
Abstract This article discusses whether supply chain due diligence laws are a suitable instrument for goals of sustainability. It uses the German due diligence law as an example and makes recommendations for the design of European rules. The emerging evidence on the effect of trade policies in global value chains suggests that, in response to such laws, firms may reorganise their supply chains away from countries that commit human rights violations. The German law, by contrast, wants firms to “Stay and Behave”, i. e. to work to improve human rights. The article discusses measures that give a “Stay and Behave” outcome its best chance.